Analisis Kesalahan Siswa dalam Menyelesaikan Soal Numerasi Ditinjau dari Self Efficacy - Indraswara, Windu Tri; Kusmaharti, Dian; Yustitia, Via (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Numeracy is the ability that a person has in using his mathematical knowledge in explaining events, solving problems, or making decisions in everyday life. This study aims to analyze and describe students' mistakes in solving numeracy problems in terms of self-efficacy. The method used is descriptive qualitative. Purposive sampling technique was used in selecting 6 subjects as subjects. Data is collected through tests and questionnaires. Data analysis used is data collection, data reduction, data presentation and conclusion. The triangulation technique used is the source triangulation technique. Based on the results of the study, seen from the aspect of self-efficacy, subjects with high self-efficacy made two types of mistakes, namely errors in understanding the problem and errors in processing skills. The subject of self-efficacy is making three types of errors, namely errors in understanding the problem, transformation errors and process skills errors. Subjects with low self-efficacy made four types of errors, namely errors in reading the problem, errors in understanding the problem, errors in process skills and errors in writing the final answer. Student self-efficacy and numeracy skills have a highly correlated and positive relationship which explains that the higher the student's self-efficacy, the higher the student's numeracy skills.